IT Encyclopedia.Com : Dictionary if I.T Terms Book.10 - Sourie, Margaret and Kaushik, Sanjay; Series Editor: Diwan, Parag; Suri, R. K. and Kaushik, Sanjay (New Dehli Pentagon Press, 2001)
Informatics plays a vital role in the economic development. Information Technology can be effectively used to monioter the performannce of economy and to enable paradigm shifts. IT Encyclopedia.Com covers the all modern aspects of Information Technology according to world wide requirements.
Includes Illustrations.
Keywords: Information Technology -- Encyclopedias